PENGARUH FINANCIAL DISTRESS TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN SUBSEKTOR BATUBARA DI BURSA EFEK INDONESIA) - KEWAL, SURAMAYA SUCI (Catholic University Musi Charitas, 2020)
This study aims to determine whether there is an effect of a sector's Financial Distress using the Altman Z-Score method on stock returns. The independent variables used in this study are Working Capital to Total Assets (WCTA), Retained Earning to Total Assets (RETA), Earning before Interest and Taxes to Total Assets (EBITTA), Market Value of Equity to Book Value of Total Liabilities (MVEBTL), Sales to Total Assets (STA) and Altman Z-Score. While the dependent variable in this study is stock returns. The data collection method in this study used purposive sampling on coal companies listed on the Indonesia Stock Exchange during the 2014-2017 period. The total sample used in this study were 18 coal companies. The data analysis method used multiple linear regression analysis. Hypothesis testing using the t test with a significance level of 5%. The results showed that WCTA, EBITTA, MVEBTL, STA, and the Altman Z-Score Category had a positive effect on stock returns, while RETA had a negative effect on stock returns.